Peran BUMN dalam Mendorong Inovasi dan Transformasi Bisnis - Angelwiss, Aullya Rieccy; Lodan, Karol Teovani; Salsabila, Lubna (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study aims to analyze the role of BUMN administration in driving innovation and business transformation. The research method is a descriptive-analytical approach, which utilizes secondary data from literature, financial reports, and other related documents. The study results indicate that the BUMN administration significantly drives innovation and business transformation in Indonesia. The following describes the main findings: BUMN administration has played an essential role in formulating and implementing long-term innovation strategies. They effectively allocate budget and personnel resources to support innovative projects. Collaboration between BUMN, the private sector, and academics in developing creative solutions is increasing. This indicates the ability of the BUMN administration to build strategic partnerships. BUMN administration also plays an active role in proposing and implementing policies that support an innovation climate. However, the study also identified several implementation challenges, such as resistance to change and rigid bureaucracy. In conclusion, innovation driven by the BUMN administration positively impacts the financial performance and global competitiveness of BUMN, indicating the success of the business transformation efforts carried out. Keywords: BUMN, Indonesia, Business Transformation